World book 2003 (Chicago World Book, 2002)
Searchable database of reference entries in the World Book encyclopedia. Includes thousands of articles as well as pictures, videos, and hundreds of detailed maps.
Discs 1 and 2: World book 2003 user guide -- disc 3: World book how to study -- disc 4:The world book student dictionary.
Keywords: Encyclopedias and dictionaries